Interactions between circadian clocks and photosynthesis for the temporal and spatial coordination of metabolism - Dodd, Antony N.; Belbin, Fiona E.; Frank, Alexander; Webb, Alex A. R. (Frontiers in Plant Science, 2015)
All plant productivity, including the food that we eat, arises from the capture of solar energy by plants. At most latitudes sunlight is available for only part of the 24 h day due to the rotation of the planet. This rhythmic and predictable alteration in the environment has driven the evolution of the circadian clock, which has an extremely pervasive influence upon plant molecular biology, physiology and phenology. A number of recent studies have demonstrated that the circadian clock is integrated very closely with photosynthesis and its metabolic products. We consider the coupling of the circadian oscillator with carbohydrate biochemistry and the connections between the nuclear-encoded circadian clock and processes within chloroplasts. We describe how this might provide adaptations to optimize plant performance in an environment that varies both predictably upon a daily and seasonal basis, and unpredictably due to the weather.